Pengaruh Modal, Upah Tenaga Kerja dan Bahan Baku Terhadap Pendapatan Industri Kerupuk - Risma Dyah Ayuningtyas; Muhammad Faisal Abdullah (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aims to determine the effect of capital, labor wages, and raw materials on the income of the cracker industry in Ngantru District, Tulungagung Regency. This research method uses quantitative methods with primary data. This study uses panel data regression analysis. The results of this study indicate that capital has a positive and significant effect on the income of the cracker industry. Labor wages have a positive and significant impact on the payment of the cracker industry. Raw materials have a positive and significant effect on the revenue of the cracker industry.